Volatile state : Iran in the nuclear age - Oualaalou, David S. (Indiana University Press, 2018)
In an age of nuclear experimentation, military conflicts, and ISIS, the Middle East is unstable, and the Iranian nuclear deal is shrouded in controversy and mistrust. How will this agreement impact US relations and strengths, not only in the region, but around the world? Will the US be challenged for world leadership? In Volatile State: Iran in the Nuclear Age, global affairs analyst David Oualaalou explores the new geopolitical landscape and how it will allow a nuclear Iran to flex its military, economic, and ideological muscles with the assistance of Russia and China. Taking under consideration how other governments have reacted to the agreement, Oualaalou provides a fresh perspective on current and future relations among the US and its current allies and provides a compelling path forward for future strategies in the Middle East. Volatile State is a "must read" to help understand the implications and future with a nuclear deal with Iran.